The impact of occipital lobe cortical thickness on cognitive task performance: An investigation in Huntington's Disease. (December 2015) - Johnson, Eileanoir B.; Rees, Elin M.; Labuschagne, Izelle; Durr, Alexandra; Leavitt, Blair R.; Roos, Raymund A.C.; Reilmann, Ralf; Johnson, Hans; Hobbs, Nicola Z.; Langbehn, Douglas R.; Stout, Julie C.; Tabrizi, Sarah J.; et al.
Abstract: Background: The occipital lobe is an important visual processing region of the brain. Following consistent findings of early neural changes in the occipital lobe in Huntington's Disease (HD), we examined cortical thickness across four occipital regions in premanifest (preHD) and early HD groups compared with controls. Associations between cortical thickness in gene positive individuals and performance on six cognitive tasks, each with a visual component, were examined. In addition, the association between cortical thickness in gene positive participants and one non-visual motor task was also examined for comparison. Methods: Cortical thickness was determined using FreeSurfer on T1-weighted 3T MR datasets from controls ( N =97), preHD ( N =109) and HD ( N =69) from the TRACK-HD study. Regression models were fitted to assess between-group differences in cortical thickness, and relationships between performance on the cognitive tasks, the motor task and occipital thickness were examined in a subset of gene-positive participants ( N =141). Results: Thickness of the occipital cortex in preHD and early HD participants was reduced compared with controls. Regionally-specific associations between reduced cortical thickness and poorer performance were found for five of the six cognitive tasks, with the strongest associations in lateral occipital and lingual regions. No associations were found with the cuneus. The non-visual motor task was not associated with thickness of any region. Conclusions: The heterogeneous pattern of associations found in the present study suggests that occipital thickness negatively impacts cognition, but only in regions that are linked to relatively advanced visual processing (e.g., lateral occipital, lingual regions), rather than in basic visual processing regions such as the cuneus. Our results show, for the first time, the functional implications of occipital atrophy highlighted in recent studies in HD. Highlights: Occipital regions performing basic and advanced visual processing examined in HD. Regionally-specific reductions in cortical thickness found in pre- and symptomatic HD. Significant associations between occipital thickness and scores on cognitive tasks. Strongest associations with cognitive scores were for advanced visual processing regions. Reduced thickness in advanced visual regions affects cognitive performance.